Development of geobot games in teaching and facilitation of form four geographical skills topics - Mohamad Amran Manining; Soon Singh Bikar Singh (Secholian Publication PLT, 2021)
The suitability of Teaching and Facilitation Strategies (PDPc) will be able to create effective and fun learning for students in schools where the ability of teachers to plan and implement various PdPc strategies is able to optimize a learning session. PDPc's student -centered strategy can provide opportunities for students to submit opinions, cultivate the attitude of always seeking knowledge and learning throughout life. Student -centered learning that requires the active involvement of students in finding and investigating problems, constructing hypotheses, designing experiments, collecting data as well as drawing conclusions to solve problems can be implemented through game -based learning. While the teacher only acts as a facilitator. This study is a design and development research using the ADDIE Model. Findings show that the implementation of the ADDIE Model in the development of Geobot Game Module makes the development of modules can be carried out systematically and produce modules relevant to the Secondary School Standard Curriculum for Geography form four set by the Ministry of Education Malaysia.